Sapatero in Marikina City enacting economies in the Philippines footwear capital - Rapisora, Ma. Concepcion B. (Quezon City Tri-College, University of the Philippines Diliman, 2018)
"This study argues that Marikina city's nostalgically popular trademark as the Philippines' footwear capital has been made possible by sapatero in the past and present who have enacted a localised economy.
This narrative begins with the story of the footwear-making industry in the sleepy town of Mariquina at the end of the nineteenth-century. Then, through archival research, analysis of previous works and participant-observation, a series of infrastructural, economic, political and social phenomena will be problematized to better understand the periods and 'perceived moments' when footwear production in the city reached national prestige and encountered obstacles. Next, ascertaining the causes of this localised industry's presently informal structures will prove that its sapatero have continued to adapt and survive amidst a series of local, national and global challenges. Lastly, the manner with which footwear in Marikina is promoted by the city's local government and represented by private retailers will be manifested. These channels, albeit faced with a number of problems, are also shown to be sources of opportunity which can improve the state of footwear-making and the lives of Marikina sapatero.
At the heart of this work are the life stories of sapatero who have witnessed a time of prosperity and periods of set-backs in this localised industry. Illuminating the lives of sapatero from which an enacted economy emerged, provides a magnified view about footwear not too captivated on the amount or cost produced, but on people who create footwear in/for the city.This study shall illustrate that it is on account primarily of Marikina's sapatero, and less on footwear as commodity, that Marikina city has enacted a localised economy. Demonstrating this here intends to inform theoretical ideas relevant to discourses on work, culture and urban theory. The research questions and objectives of this study are a means to dialogue with such broad base of conceptual aggregates.
The case of footwear in Marikina city exemplifies how a city is best understood in its own terms rather that pitting it vis-à-vis "global standards" of economic progress. The survival of a dynamic network of sapatero, detached from the global competition of footwear commodities, while neither directly contributing to the financial revenue of the city nor the country's, can be interpreted as a certain form of shielding which is decent evidence of the survival of a city's localised industry rather than a sign of its decline." --Author
Thesis (Doctor of Philosophy in Philippine Studies)--University of the Philippines Diliman
Keywords: Footwear industry -- Marikina(Philippines); Marikina (Philippines) -- History